Optimized Resource Allocation Using Machine Learning Techniques - Tamil Selvi K, Aparna.K.S, Jayanthi.P (International Journal of Advanced Science and Technology, 2020)
Resource allocation in any computing environment provides scope for optimization. To allocate hardwarein a particular organization (or) institution in an efficient way, refined grasshopper optimizationalgorithm is used. In grasshopper optimization algorithm, randomness is not achieved properly. Toachieve the randomness, Levy search algorithm is used. Levy search algorithm is the random searchalgorithm where the probability distribution of a random search walk and it is used to provide randomfactor efficiently. This result is compared with the results obtained from cuckoo search algorithm over therequests. The experimental result shows that Improved Grasshopper optimization algorithm gives the bestresult.